INTEGRATIVE BASKETBALL PERIODIZATION AND ADAB-BASED CHARACTER DEVELOPMENT: AN EMPIRICAL STUDY OF THE EXTRACURRICULAR PROGRAM AT PONPES MINHAJUL HAQ PURWAKARTA - Rizaldy Alpiansyah; Agus Salim; Muslihin (Al Musa’adah : Journal of Community Service STAI Minhajul Haq, 2026)
This evaluative study documents the systematic implementation of a high-performance basketball extracurricular program at Ponpes Minhajul Haq, Purwakarta. The research focuses on measuring the efficacy of a structured training model against two primary variables: motor-physiological competence and character integrity (Adab). Utilizing an Action Research framework with a One-Group Pretest-Posttest design, the study involved 50 male students over a 36-week macrocycle. Evaluation instruments included digital inventory audits, AAHPERD Basketball Skills Testing, and longitudinal character observation rubrics. Results indicate a significant 37.8% increase in aerobic capacity (VO2 Max) and a 42% improvement in fundamental technical mastery. Furthermore, the discussion highlights how athletic discipline contributes to enhanced academic resilience and emotional stability. This article proposes the "Student-Athlete-Santri" model as a prototype for physical education in modern Islamic boarding schools.